Narrowband ultraviolet B irradiation increases the serum level of vitamin D3 in patients with neurofibromatosis 1 - Nakayama, Juichiro; Imafuku, Shinichi; Mori, Tatsuki; Sato, Chiemi (Journal of dermatology, 2013)
The serum vitamin D3 levels in patients with neurofibromatosis 1 has been reported to be significantly lower than that in control subjects, and the level of vitamin D3 reversely correlates with the severity of neurofibroma formation. We found that narrowband ultraviolet B (NB‐UVB) irradiation increased the serum level of 1,25(OH)2 vitamin D3 in patients with neurofibromatosis 1. The difference in the 1,25(OH)2 vitamin D3 levels between patients who had received irradiation for more than 18 months and those who had no irradiation was highly significant. Time‐course analyses of the serum vitamin D3 levels in the patients who were enrolled after informed consent revealed that the levels became higher significantly after 6 months of irradiation. It is suggested that NB‐UVB irradiation is effective for increasing the serum level of vitamin D3 in patients with neurofibromatosis 1, which may be of benefit for skin symptoms such as pigmented macules or neurofibromas.